Maximizing Potential: Total Quality Manamenet (TQM) Implementation in 'Aisyiyah Women Entrepreneurs' Small Medium Enterprises (SMEs) - Sentika, Sarah; Arissaputra, Rivaldi (CV. AFDIFAL MAJU BERKAH, 2023)
The rapid growth of Small and Medium Enterprises (SMEs) in Indonesia, with 64.2 million businesses employing 97% of the workforce by 2021, has intensified competition, necessitating enhanced management strategies. This study focuses on the Bandung region, which boasts the highest number of SMEs in West Java. To maintain quality and competitiveness, SMEs are encouraged to adopt Total Quality Management (TQM). TQM is a commitment to delivering the best to customers, emphasizing continuous improvement and customer satisfaction. This community engagement project employed the Discovery Learning Model and Problem-Based Learning, using a digital module on Total Quality Management. The engagement involved 20 'Aisyiyah Women Entrepreneurs, primarily from Bandung. The sessions stimulated active discussion and highlighted the importance of TQM for SMEs. Challenges were identified, notably the adoption of digitalization among Generation X employees. The project emphasizes that TQM is vital for SME development, particularly in human resource management. Moreover, the learning model used encourages active participation and discussion, enabling participants to share real challenges faced by SMEs. Acknowledging the significance of TQM, this project aims to equip SMEs with the tools needed to thrive in the highly competitive landscape, setting the stage for their sustainable growth and success.